The Importance of English Language Proficiency In International Tourism Enterpreneurship - Agustina (Universitas Muhammadiyah Makassar, 2025)
This study explores the significance of English language proficiency as a strategic asset for entrepreneurs in the international tourism sector. As the global lingua franca, English facilitates communication with international clients, enhances service quality, and enables market expansion. Employing a qualitative descriptive method, the study draws from interviews and open-ended questionnaires with tourism entrepreneurs to examine how English proficiency impacts business operations, customer interactions, and growth potential. Findings reveal that while many entrepreneurs recognize the importance of English, challenges such as low confidence, limited vocabulary, and lack of formal training persist. The study concludes with strategic recommendations to improve English communication skills in tourism, advocating for tailored language training programs and supportive policy interventions.